Impact of a 7-day short peptide diet on gut microbiota and metabolomics in septic mice - Zuo, Dan; Zuo, Binyu; Wang, Liuyang; Hu, Dabi; Yang, Yang; Chen, Yong; Huang, Biao (Frontiers in Nutrition, 2025)
ObjectiveOur study aim is to explore the mechanisms of short peptide passages on intestinal dysfunction in septic mice utilizing a metabolomics approach, which provides a new scientific basis for the clinical study of sepsis.MethodsMices were allocated at random into four groups: control (Con), cecal ligation and puncture followed by one, three or 7 day short-peptide-based enteral nutrition group (CLP + SPEN1), (CLP + SPEN3), and (CLP + SPEN7) groups. A liquid chromatography-mass spectrometry-based metabolomics method was used to analyze changes in serum metabolites in septic mice.ResultsShort peptides showed effectiveness in reducing symptoms, mucosal inflammation, and intestinal function damage scores in septic mice. The 16sRNA analysis showcased significant variances in the distribution of bacterial communities between the CLP + SPEN1, CLP + SPEN3, and CLP + SPEN7 groups. At the phylum level, statistically significant variances in the relative abundance of Proteobacteria, Firmicutes, and Bacteroidetes were recognized. The metabolomics analysis results showed significant separation of metabolites between the CLP + SPEN1 and CLP + SPEN3 groups, as well as significant differences in metabolite profiles between the CLP + SPEN3 and CLP + SPEN7 groups. Utilizing a differential Venn diagram, four metabolites were commonly different; 10-heptadecanoic and dodecanoic acids had statistical significance. The abundance of both dodecanoic and lactic acid bacteria was negatively associated at the genus level.ConclusionShort peptides were found to promote the growth of beneficial bacteria, Lactobacillus and uncultured_bacterium_f_Muribaculaceae, while reducing intestinal metabolites such as Dodecanoic acid and 10-Heptadecenoic acid. Moreover the Lactobacillus may play a significant therapeutic role in the treatment of sepsis. However, due to the limited number of experimental samples, the exact mechanism of action of short peptides awaits further confirmation.